L’européanisation fictive des Phanariotes - Yannis Xourias (Cahiers Balkaniques)
The Greek 18th century is “the century of Phanariots”, who are under the influence of European culture and bring fashions from Europe to Constantinople. Such a fashion is the reading of sentimental novels. In The Consequences of Love (1792), the first Greek collection of original love stories, the daily life of the Phanariots is depicted according to the conventions of European sentimental literature. Thus the ‘Phanariots’ Europeanization is achieved not only through reading, but also through fiction. In other words, the Hellenization of sentimental literature functioned also as a fictional Europeanization of the Phanariots.